Demographic Transition in Kerala: Facts and Factors - T. N. Krishnan (Economic and Political Weekly, Vol. 11, No. 31/33, 1976)
This paper examines the recent trends in birth, death and infant mortality rates - the three key demographic parameters which define the demographic pr4ofile of a region - for Kerala and analyses the role of factors like literacy, the age of inarriao'e, thle avnailabilitzl of medical care facilities, etc, in this demographic transition. Part I of the paper examines the birth rate in Kerala in relation to tne rates prevailing in the other states, analyses the magnitude of the change in it in recent years and isolates the factors that might have contributed to its decline. In part II, the trends in mortality rates and the factors which might have con- tributed to their decline are analysed. Part lII attempts io drawz some policy lessons which may be of relevance for general population policy in developing countries